Questions in English as a Medium of Instruction versus non-English as a Medium of Instruction Lectures (GIST – Education and Learning Research Journal, 2017)
University lectures are by far the most common method of teaching at Spanish universities. More recently, however, this knowledge transmission has become increasingly interactive. Students’ participation and verbal output becomes especially important in classes where the language of instruction is not the students’ mother tongue but a second or foreign language such as English since it gives them the opportunity to produce output in that second language. One of the ways to allow for students to participate is the lecturer’s use of questions. The aim of this study is to compare the same lecturer’s use of questions in her mother tongue or L1 (Spanish) versus her lectures in English (L2). More specifically, I intended to answer the following research question: Is the frequency and type of questions affected by the language of instruction (Spanish vs. English)? It is hypothesized that questions will be more frequent in English so as to boost verbal interaction between the lecturer and the students and allow them to produce verbal output in English. To test this hypothesis, a group of six lectures by the same lecturer (3 in English and 3 in Spanish) was analyzed, involving two groups of students taking the same subject albeit in one of these two languages. According to expectations, results show that English lectures display a slightly higher frequency of questions than those in Spanish. However, a qualitative analysis also reflects interesting aspects of the type (and characteristics) of questions in English.
Keywords: Questions; English as a Medium of Instruction; EMI; Tertiary Education